Investigating Jan van Eyck - Foister, Susan, 1954-; Cool, Delphine; National Gallery (Great Britain) (Turnhout : Brepols, 2000)
Essays, chiefly delivered at the Jan van Eyck Symposium, held at the National Gallery, 13-14 March 1998.
"The king of painters' / Catherine Reynolds -- The Arnolfini double portrait / Lorne Campbell -- Jan van Eyck's Dresden triptych / Uta Neidhardt and Christoph Schölzel -- The Saint Barbara / Rachel Billinge, Hélène Verougstraete and Roger van Schoute -- The Virgin and Chancellor Rolin and the Office of Matins / Philippe Lorentz -- Assessing the evolution of van Eyck's iconographythrough technical study of the Washington Annunciation, I / E. Melanie Gifford -- Assessing the evolution of van Eyck's iconography through technical study of the Washington Annunciation, II : new light on the development of van Eyck's architectural narrative / Carol J. Purtle -- Jan van Eyck's handwriting / A.L. Dierick -- Examining Jan van Eyck's underdrawing / Rachel Billinge -- Van Eyck's technique : the myth and the reality, I / Ashok Roy -- Van Eyck's technique : the myth and the reality, II / Raymond White -- Frames and supports of some Eyckian paintings / Hélène Veroogstraet and Roger van Schoute -- Sculpture and the van Eycks : some Mosan parallels / John Steyaert -- Dress in van Eyck's paintings / Margaret Scott -- Silk textiles in the paintings of Jan van Eyck / Lisa Monnas -- Anselm Adornes and his daughters : owners of two paintings of Saint Francis by Jan van Eyck? / oël Geirnaert -- Jan van Eyck's painting in Italy / Paula Nuttal -- An approach to looking at Eyckian drawings / Stephanie Buck -- The use of workshop drawings by Jan van Eyck and his followers / Sue Jones.
Chiefly papers presented at the Jan Van Eyck Symposium held at the National Gallery, Mar. 13-14, 1998 to coincide with the London showing of the exhibition 'Recognizing van Eyck' organized by the Museo civico Turin and the Philadelphia Museum of Art.
Series information from publisher's website, viewed June 18, 2017.
Includes bibliographical references and index.
Keywords: Eyck, Jan van, -- 1390-1440 -- Congresses; Eyck, Jan van, -- 1390-1440 -- Criticism and interpretation; Eyck, Jan van, -- 1390-1440.; Eyck, Jan van, -- 1390-1440 -- Critique et interprétation; Eyck, Jan van, -- 1390-1440.; Schilderkunst; Conference papers and proceedings; Criticism, interpretation, etc